Bio Briket Cangkang aleurites moluccana Melalui Gelombang Elektromagnetik dengan Varian Daya dan Durasi Waktu Karbonisasi - Rini Kartika Dewi; Mohammad Istnaeny Hudha; Ferry Darmawan; Dendy Wono Prasetyo (Program studi Teknik Kimia UNS, 2020)
Abstrak. Biobriket adalah sumber energi yang berasal dari biomassa dan dapat digunakan sebagai bahan bakar padat pengganti minyak bumi dan energi lain yang berasal dari fosil. Biobriket merupakan salah satu solusi altenatif yang cukup efektif dan efisien dalam menghadapi krisis sumber energi, salah satu diantaranya adalah dengan mengoptimalkan cangkang kemiri sebagai biobriket. Tujuan dari penelitian ini adalah mengetahui pengaruh gelombang elektromagnetik microwave terhadap kualitas biobriket cangkang kemiri melalui varian daya dan durasi waktu karbonisasi. Dari hasil Analisa menunjukkan adanya pengaruh daya dan durasi waktu karbonisasi terhadap karakteristik dari biobriket cangkang kemiri. Dari analisa didapatkan hasil sebagai berikut : kandungan kadar air sebesar 6.43 %, kadar abu : 7.48 %, Total Karbon yang didapatkan : 42.53 %, Volatile matter : 41.91 % dan nilai kalor dari biobriket adalah : 5706,24816 kal/gramAbstract. Bio briquette is a source of energy derived from biomass and can be used as a solid fuel instead of petroleum and other energy derived from fossils. Bio briquettes are one of the alternative solutions that are quite effective and efficient in dealing with the crisis of energy sources, one of which is by optimizing the pecan shell or shell of Aleurites moluccana as a bio briquette. Pecan shell is a waste that is very abundant in Indonesia and can be used as a solid fuel that is environmentally friendly and has a high calorific value. The purpose of this study was to determine the influence of microwave electromagnetic waves on the bio briquette quality of pecan shells through power variants and the duration of carbonization time. The stages are pecan shell cleaning, carbonization process with microwave electromagnetic waves at predetermined power and duration of time (0.5, 1, 1.5 and, 2 hours), the process of crushing into charcoal with disk mill equipment, mixing with adhesive material with a ratio between the mass of charcoal and adhesive material 80:20 (b/b), bio briquette printing and the last stage is drying with sunlight for 2 days. From the analysis obtained the most optimum results are at 440 watts of power for 1 hour with the following results: water content of 7.30%, ash content: 7.48%, Carbon Bound obtained: 73.31%, Volatile matter: 30.23% and, the calorific value of bio briquette is: 5706.24816 cal/gramKeywords: bio briquette, pecan shell, electromagnetic wave, carbonization, microwave